Art-Image Contents of Lexeme “Time” in the Poetic Language of J. Brodsky - Ekaterina Gennadievna SHTYRLINA; Lilia Renadovna AHMEROVA; Li YING (Astra Salvensis, 2019)
The article deals with the study of the peculiarities of the author’s individual semantic filling of the lexeme 􀇯􀇽􀇲􀇹􀈌 / time in the poetic language of J. Brodsky. 1 Time is one of the system-forming abstract entities that play an important role in the person’s realization of the world’s organization of nature and society of people. The results of cognition of the properties of time find a vivid expression in the very language, so the study of linguistic temporal structures allows us to objectify the mental forms and comprehend the conceptualization of the world by human consciousness and mentality. A special realization of time lexemes is in literary texts, because individualized meanings generated by the text itself along with the main nominative generalized meaning are realized in linguistic units. From this insight into the textual behaviour of linguistic units, it logically follows that each particular text has its own individual, functional-semantic field of artistic time inherent only in it, the units of which realize the temporal category in a special, original and unique way. In this connection, a special interest for our study is the corpus of poetry by J. Brodsky, which gives a metaphorical, axiologically coloured, emotionally marked image of time. As a result of the research it has been found that the lexeme 􀇯􀇽􀇲􀇹􀈌 / time in the texts of I. Brodsky has both usual meanings and occasional ones. In most contexts, the traditional interpretations of the temporal lexeme are enriched in the poet’s works with additional meanings connected with the author’s individual interpretation of temporal reality, as a result of which new original metaphorical images arise that reflect the specificity of the writer’s worldview. Thanks to the special image system, the anthropomorphic depiction of temporal aspects, the abundance of associative parallels of the lexeme 􀇯􀇽􀇲􀇹􀈌 / time is perceived in the literary world of J. Brodsky as a multidimensional, original temporema, saturated with poetic meanings. Research methods: descriptive-analytical method, method of contextual analysis of literary text, method of interpretation of literary text, method of continuous sampling.